Answer:
LHS=(1-sin60)/cos60
=(1-√3÷2)/1÷2
=2(1-√3÷2)
=2-√3
RHS=(1-tan30)/(1+tan30)
={1-(1÷√3)}/{1+(1÷√3)}
={(√3-1)/√3}/{(√3+1)/√3}
=(√3-1)/(√3+1)
={(√3-1)(√3-1)}/{(√3+1)(√3-1)}
=(3-√3-√3+1)/(3-1)
=(4-2√3)/2
=2-√3
Brainliest?
Answer:
220
Step-by-step explanation:
Answer:
no, this is not a function
Step-by-step explanation:
i hope this helps :)
Answer:
the answer is A.) or (3 and one-half, negative 4)
Answer:
2c - 18x + 74/5
Step-by-step explanation:
<u>Step 1: Distribute
</u>
2(c + 7) - 18x + 4/5
(2 * c) + (2 * 7) - 18x + 4/5
<em>2c + 14 - 18x + 4/5
</em>
<u>Step 2: Combine like terms
</u>
2c + 14 - 18x + 4/5
<em>2c - 18x + 74/5
</em>
Answer: 2c - 18x + 74/5